Inflation synchronisation strengthening in Europe in post-quantitative easing and post-pandemic high inflation times: consequences for single monetary policy management - Budová, Jana; Šuliková, Veronika; Siničáková, Marianna (Zielona Góra: Faculty of Economics and Management Press)
This paper aims to find out whether the inflation rates of individual European Union (EU) countries are synchronised with those of the EU as a whole and with the euro area (EA). Another objective is to examine the mutual inflation interconnections and its synchronisation across countries. We use the Minimum Spanning Tree (MST) and cross-correlations (C-C).
Keywords: inflation transmission; inflation synchronisation; quantitative easing; Minimum Spanning Tree; cross-correlation